A study analyzing the relationship of emotional intelligence to academic success assessment and stress, depression, anxiety of medical students - Alka D. Gore; Vinayak A. Jadhav (Al Ameen Medical College, 2021)
Background: In the life of medical students, while taking the education or doing clinical practice, Intelligence Quotient as well as Emotional Intelligence, both are important to achieve higher skills as well as to improve doctor-patient relationships. This study was conducted to find relation between Emotional Intelligence with Academic Success Assessment as well as with stress, depression and anxiety. Methodology: A cross-sectional study was conducted in a medical college. A questionnaire was used to collect data, which is divided into four sections: socio-demographic factors, Emotional Intelligence trait questionnaire, DASS scale and the Academic Success Assessment questionnaire. ANOVA and Tukey's post-hoc test, Chi-square test, Fisher's exact test and binary logistic regression were applied using SPSS-22 for statistical analysis. Results: Stress and depression are significantly associated factors for emotional intelligence. EI, stress, depression and anxiety scores are significantly higher in students having personal and academic issues, or those with disturbed routine. According to different logistic models, the log of the odds of a student being stressed, depressed and having anxiety was positively and significantly related to EI. Conclusion: EI is an important significant factor in the academic life of medical students. EI scores were significantly higher in the students having stress, depression or anxiety.